Hinge Craniotomy for Traumatic Brain Injury: Surgical Technique - Jain, Chirag; Devi, Bhagavatula Indira; Bhat, Dhananjaya I.; Shukla, Dhaval; Konar, Subhas (Indian Journal of Neurosurgery, 2024)
Hinge craniotomy has been described as an alternative to decompressive craniectomy for the control of intracranial pressure in traumatic brain injury and stroke. In this study, the authors highlight critical steps in performing a hinge craniotomy and present a clinical case of a patient with traumatic brain injury.
Keywords: hinge craniotomy; traumatic brain injury; intracranial hypertension